1927: Earthquakes, Unemployment, and the Infrastructure of Mandate Palestine. Issue 1 (2nd January 2023) - Irving, Sarah
Abstract: Although Lord Plumer's tenure as high commissioner for Palestine (1925–28) is sometimes characterized by mainstream Euro-American histories as a period of comparative peace, the year 1927 saw two major disruptions: the Jericho earthquake in July, which caused serious damage to towns and cities including Jerusalem, Nablus, and Lydda; and unrest among Jewish immigrants who found that the local economy had no jobs to offer them—or at least not ones at the European rates of pay to which they were accustomed. This article explores the ways in which each of these crises intersected with Palestine's infrastructure—in particular its railways, roads, and housing stock. I argue that the disparate ways in which the British administration approached earthquake victims versus the unemployed, the help it offered (or failed to offer), and the policies it implemented are telling about the nature of British governance in Palestine in the mid-1920s and British administrative priorities and concerns. The Mandate authorities' responses to the quake—characterized by selective negligence—reveal the colonial administration's weakness, the contested ways in which colonial structures were shaped and operated in the early Mandate period, and the extent to which maintaining a facade before other colonial powers and the League of Nations outweighed substantive action.